Marburg and Ravn Virus Infections Do Not Cause Observable Disease in Ferrets. (8th June 2018) - Wong, Gary; Zhang, Zirui; He, Shihua; de La Vega, Marc-Antoine; Tierney, Kevin; Soule, Geoff; Tran, Kaylie; Fernando, Lisa; Qiu, Xiangguo
Abstract: Ferrets are used for studying infections with wild-type Ebola virus isolates. Here, we investigated whether these animals are also susceptible to wild-type isolates of Marburg virus (MARV). Ferrets were challenged intramuscularly or intranasally with MARV strain Angola and monitored for 3 weeks. Unexpectedly, the animals neither showed observable signs of disease nor died of infection, and viremia was not detected after challenge. All animals were seropositive for MARV-specific immunoglobulin antibodies. Confirmatory studies with MARV strain Musoke and Ravn virus yielded the same outcomes. Therefore, ferrets may be of limited usefulness for studying the pathogenesis of MARV and Ravn virus infections.